2020
DOI: 10.11606/s1518-8787.2019053001466
|View full text |Cite
|
Sign up to set email alerts
|

On-demand cesarean section: assessing trends and socioeconomic disparities

Abstract: OBJECTIVE: to measure prevalence, evaluate trends and identify socioeconomic differences of on-demand cesarean section in the municipality of Rio Grande (RS), extreme south of Brazil, in 2007, 2010, 2013 and 2016. METHODS: all the puerperae residing in this municipality who had cesarean deliveries in one of the only two local maternity hospitals in the period 01/01-31/12 of the aforementioned years were part of this transversal study. Puerperae were interviewed using a single, standardized questionnaire at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Likewise, a study performed in Brazil concluded that C-sections were more common among women at low risk of maternal or fetal death, suggesting, once again, that the option for this type of delivery was mostly elective 7 . A previous publication also using data from the "Estudos perinatais" observed that C-section occurrence by request of pregnant women doubled, from 11% in 2007 to 22% in 2016 21 . Only these percentages of caesarean sections alone already exceed the justifiable limit published by WHO.…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, a study performed in Brazil concluded that C-sections were more common among women at low risk of maternal or fetal death, suggesting, once again, that the option for this type of delivery was mostly elective 7 . A previous publication also using data from the "Estudos perinatais" observed that C-section occurrence by request of pregnant women doubled, from 11% in 2007 to 22% in 2016 21 . Only these percentages of caesarean sections alone already exceed the justifiable limit published by WHO.…”
Section: Discussionmentioning
confidence: 95%
“…One explanation for these findings could be that some of the women in Groups 1 and 3 may have been misclassified and could potentially belong to another group with a higher risk of caesarean delivery or maybe some of them had an intervention carried out without any clear medical indication. This is because maternal request or the physician’s preference have consistently been identified as a cause for growing rates of caesarean sections in recent decades [ 21 23 ] and this is a common practice in Brazil [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these considerations, some significant demographic features such as education, income, and familiarity with the medical system were not included in the analysis. Carlotto et al 33 demonstrated that lower socioeconomic status correlated with higher rates of CS. Amjad et al 34 showed a relationship between a lower level of education and a higher rate of CS.…”
Section: Discussionmentioning
confidence: 99%